AB1208 Educational Needs for Young Rheumatologists in Spain. (9th June 2015) - Rosales, Z.; Andrés, M.; Sivera, F.; Loza, E.
Abstract : Background: The identification of the educational and training needs of residents and young rheumatologists appears essential to develop appropriate courses and educational programs. Methods: Online survey, sent by e-mail to all Spanish members of EMEUNET (Emerging EULAR Network) and JOVREUM (young rheumatologists group of the Spanish Society of Rheumatology) groups, as well as to any young rheumatologist (aged below 40 years old) e-mail contact that these members had. The study period was July-October 2014. The survey content was adapted from the EMEUNET "Educational needs for young European rheumatologists" survey [1], and had three sections: i) respondents' data (demographics, training and professional status); ii) objectives and learning needs (clinical, research, and laboratory training and skills); and iii) awareness and evaluation of the Spanish Society of Rheumatology educational course offer (including obstacles hindering participation and preferences on learning modalities). Likert semiquantitative scales were used to collect data. A descriptive analysis was performed. Results: Data was obtained from 52 respondents, 66% women, and 63% aged 31-35 years old. Over 70% were rheumatologists working in Spain. Regarding clinical knowledge, the respondents showed a high interest (>60%) in obtaining additional training in systemic autoimmune diseases, rheumatoid arthritis, and spondyloarthritis; and a moderate interest (40% to 60%) in pediatric rheumatology, crystal arthritis, and osteoporosis. Regarding practical skills, a high interest in additional training in ultrasound, conventional X-ray, capillaroscopy, arthrocentesis, and clinical examination was noted; for other practical skills they showed a moderate interest. The respondents showed a low interest in receiving further training in generic skills. Regarding scientific skills, they showed a high interest in scientific writing, paper reviewing, research project designing, research results communication, systematic literature reviewing, statistics, and research methodology. No specific learning modality could be identified. Regarding the Spanish Society of Rheumatology course offer, it was widely known, but 68% of respondents were partially satisfied with it; main barriers to participate in these courses were lack of funding and frequent appliance refusals. Regarding research support strategies, they were highly interested in travel bursaries for international meetings, grants for stays at national or foreign units, and PhD programs funding. No significant differences between trainees and rheumatologists were noted. Conclusions: This survey reveals a high interest in both clinical and research training of young Spanish rheumatologist, but the low number of respondents might be a limitation. Though the Spanish Society of Rheumatology educational offer is generally known, some barriers hindering participation have been identified. References: Beyer C. Ann Rheum Dis 2014;73(Suppl2): 111. Disclosure of Interest: None declared